7(p-1)=3(p-3)

Simple and best practice solution for 7(p-1)=3(p-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(p-1)=3(p-3) equation:



7(p-1)=3(p-3)
We move all terms to the left:
7(p-1)-(3(p-3))=0
We multiply parentheses
7p-(3(p-3))-7=0
We calculate terms in parentheses: -(3(p-3)), so:
3(p-3)
We multiply parentheses
3p-9
Back to the equation:
-(3p-9)
We get rid of parentheses
7p-3p+9-7=0
We add all the numbers together, and all the variables
4p+2=0
We move all terms containing p to the left, all other terms to the right
4p=-2
p=-2/4
p=-1/2

See similar equations:

| x+6=15.6 | | 144x-324=0 | | 3/x+5/3=5 | | 5x-32=2x-2 | | -5/15+2m=-3/15 | | -115+15x=5x+55 | | 4z+5=z+14 | | x-1.2=6.3 | | 6+4/5b+9/10b=8+2/10b | | x-31/2=-52/3 | | 6x=14-10x | | 3/8×n=6 | | -9x-37=-6x+14 | | 11+5y=21 | | 14x+2x-8=2x+20 | | 16+5y=21 | | 8x-2=6x-18 | | 98x^2+28x+1=0 | | 0.4(x+3)=4 | | -5x-161=99-15x | | 62.50*0.18=x | | -66-6x=62-10x | | 1/5g+3=9 | | 4^3x-1=8^x+4 | | 1/5g=9 | | 2=(-9x+21)-5 | | 1/2x=-17 | | -3/4v+4/5=7/8 | | t-9.95=5.45 | | 5.1+d=14.2 | | X^2-9x+11x+12=180 | | (6x-35)(4x+11)=x |

Equations solver categories